Watching you : a novel - Jewell, Lisa (Atria Books, 2018)
"Melville Heights is one of the nicest neighborhoods in Bristol, England. It's the sort of place where doctors and lawyers and old-money academics live. It's not the sort of place where people get stabbed in the back thirty times with a kitchen knife in their own homes. Someone must have seen something. Newlywed Joey Mullen, for example, recently returned from four years working in Ibiza. She and her husband Alfie are eager to find a place of their own in her hometown. But Joey finds herself distracted by the man next door, Tom Fitzwilliam. He's the principal of the local high school, twice her age, and devastatingly attractive. What starts as an innocent infatuation soon escalates into fixation, and before long, Joey can't keep her eyes off of Tom. Or the principal's son, Freddie, who dreams of working as a spy, and has been developing his surveillance skills by keeping meticulous logs of the coming and goings in the area. And, as he approaches his fifteenth birthday, his attention--and his lens--are turning more and more towards the local women. Or perhaps single mother Frances Tripp, who has long been convinced she is being stalked. Her teenage daughter Jenna is worried these delusions are signs of her mother's deteriorating mental health, particularly now that her paranoia has found a specific target: Tom Fitzwilliam. Frances is determined to keep an eye on him until she can prove that he is behind her persecution. Twenty years earlier, a schoolgirl writes in her diary, charting her doomed obsession with a handsome young English teacher named Mr. Fitzwilliam. Nobody knows why this horrific murder was committed, but someone in Melville Heights knows who did it. As the community's fearful eyes turn on each other, the question remains: Who else is watching?"--